Cyberbullying Pada Aplikasi Tiktok Ditinjau Dari Hukum Pidana dan Fiqh Empat Madzhab - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Azbarkati, Landung; Danu Novianto Nugroho; Wishnu Nugroho (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2024)
The growth of information technology has introduced challenges like cyberbullying, especially on platforms like TikTok. The real-time nature of TikTok and insufficient moderation exacerbate the psychological harm caused to victims. In Indonesia, cyberbullying is a criminal offense under Law Number 19 of 2016 (ITE Law) as it violates human rights. From an Islamic perspective, it is seen as a serious sin, contradicting Islamic moral values. The four major Islamic schools of thought—Hanafi, Maliki, Shafi'i, and Hanbali—guide punishing offenders, ranging from fixed (hudud) to discretionary (ta'zir) penalties depending on the severity of the offense. This study uses a doctrinal legal approach and library research to examine cyberbullying on TikTok from the perspectives of both criminal law and Islamic jurisprudence. The findings highlight that integrating the principles of positive law with Islamic jurisprudence could create a more holistic and effective framework for addressing cyberbullying. A combined approach can strengthen anti-cyberbullying policies, fostering a safer digital environment. Additionally, promoting education that emphasizes Islamic values such as respect can help prevent cyberbullying. The study recommends increasing public awareness, integrating Islamic and positive legal principles into policies, and improving law enforcement’s capacity to address cyberbullying more effectively.